AKIL RİSALELERİ GELENEĞİ VE BU GELENEK İÇİNDE EBÜ’L-BEREKÂT EL-BAĞDÂDÎ’NİN AKIL RİSALESİ - Ferruh Özpilavcı (İslami İlimler Dergisi)
Discussions of Intellect, originating from Aristotle’s De Anima, caused a series of works to come, which can be collected under the title of ‘treatises of intellect’ through ‘the expositor’Alexander Afrodisias who handled this issue in an independent work named De Intellectu. Especially the theory of separate active intellect which Alexander set forth in his treatise as a producer cause of human intellect was discussed intensively by many of the commentators like Themistius and John Philoponus, and had repercussions in the Islamic world especially in Kindî and Farabî’s treatises of intellect. One of the most remarkable examples in this tradition of treatises of intellect was presented by Abu’l-Barakât al-Baghdâdî, the philosopher with Jewish origin but converted to Islam and well-known with his considerable critiques to peripatetic philosophy, in his treatise in which he tried to reconcile the religious, theological and philosophical views on the intellect in the light of the verses of Koran and hadith. In this article, the views advanced on the intellect, the comprehensive subject matter related to several areas from epistemology to psychology, cosmology to eschatology, and ethics to prophecy, have been generally discussed on the basis of treatises of intellect. In this context, especially Baghdâdî’s views have been examined focusing on his treatise ‘Sahîhu edilleti’n-nakl fî mahiyyeti’l-akl (the true religious arguments on the essential character of intellect)’. His other works have also been referred in the scope of this article.